Interest of the Students in Lecturer's Teaching Performance in the Hybrid Classroom - Aeni, Nur; Saud, Syukur; Yunus, Muhammad; Strid, John Evar (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. This study sought to determine whether students in the English Language Study Program are interested in the lecturer's teaching performance in learning English for Tourism subject for hybrid classroom, as well as the impact of the lecturer's teaching performance on students' interest in learning English for Tourism subject. This study employed a combination of quantitative and qualitative studies In the academic year 2021/2022, the population consisted of students of English Language Education (ELE) study program. There were 260 ELE students as the population.  By addressing purposive sampling, which has some categories namely: the students who were enrolling in English for Tourism subject; the students were eager to participate in this study. There were 52 students involved as the subject.  In order to obtain the data, the researchers utilized the survey questionnaires and semi-structured interview as research tools. Testing the hypotheses provided information on the relationship between lecturer’s teaching performance and students’ interest in learning English for Tourism subject. SPSS version 26 for Windows was utilized by the researcher to handle and analyze the data for this study.  The findings of this study demonstrate that the majority of questionnaire computations result in. According to the findings of the interviews, the majority of students believe that the teacher's teaching performance has an impact on students' interest in learning the English for Tourism’ subject. Some implications has been  proposed by the researchers namely: the beginning to build effective plans, well-prepared lecturers need to have a thorough understanding of the work at hand, they are: the language appropriate for the level; the appropriate skills; the appropriate learning resources; the appropriate teaching stages and methods; A variety of activities; Classroom management abilities; grab your online and offline studentsKeywords: Students’ Interest; Teaching Performance; Hybrid Classroom